Association between blood urea nitrogen-to-creatinine ratio and mortality risk in critically ill patients with ventilator-associated pneumonia: a retrospective study - Lei Liu; Qiuli He; Muhuo Ji; Jun Liu (Frontiers in Medicine, 2026)
Background Ventilator-associated pneumonia (VAP) is a frequent complication of mechanical ventilation that increases mortality and strains healthcare resources. The blood urea nitrogen-to-creatinine ratio (UCR) is a readily available marker of renal function and hydration status. We investigated the association between UCR and short-term mortality in critically ill patients with VAP. Methods This retrospective cohort study used data from the MIMIC-IV database and included 2,037 patients with VAP admitted to the intensive care unit (ICU). Patients were categorized into three groups according to tertiles of the blood urea nitrogen-to-creatinine ratio (UCR; T1–T3). Baseline characteristics, laboratory findings, comorbidities, and clinical outcomes were collected within the first 24 h after ICU admission. The primary outcomes were all-cause mortality at 30 and 60 days post-admission. Kaplan–Meier survival analysis and multivariable Cox regression were used to assess the relationship between UCR and mortality, and a restricted cubic spline analysis was performed to explore non-linear associations. Results The median UCR among the 2,037 patients was 22.09. Kaplan–Meier analysis showed significant differences in survival across UCR tertiles (log-rank p < 0.05), with the highest mortality in the highest tertile (T3). In multivariable Cox regression, after full adjustment the highest tertile (T3) remained independently associated with increased 30-day mortality (HR 1.63, 95% CI 1.14–2.33) relative to the middle tertile (T2); the risk for the lowest tertile (T1) was significant after adjustment for demographics and comorbidities (HR 1.41, 95% CI 1.03–1.94). Restricted cubic spline analysis revealed a non-linear, U-shaped association between UCR and mortality, suggesting a threshold effect. Conclusion In the primary cohort, the highest UCR tertile remained associated with higher 30-day mortality after full adjustment, whereas the lowest tertile did not. In the sensitivity model additionally conditioning on first-24-h KDIGO stage and non-renal SOFA, T3 remained associated with mortality (HR 1.68, 95% CI 1.28–2.22), while T1 did not (HR 1.18, 95% CI 0.87–1.60). Adding UCR did not significantly improve cross-validated discrimination beyond SOFA (ΔAUC 0.021, 95% CI −0.004 to 0.045) or SAPS II (ΔAUC −0.001, 95% CI −0.015 to 0.014). UCR should therefore be interpreted as an associative risk marker rather than a causal or treatment target.